The Development of Rural America - Brinkman, George (University Press of Kansas, 1974)
In the last decade, rural development emerged as one of the prominent challenges facing the Unite States. Strong support for rural development is now found in both major political parties and at federal, state, and local levels. There is little doubt that the development of rural America will become even more important in the future.Despite unprecedented growth, both urban and rural areas in the United State are greatly deficient in many aspects of quality living conditions. The nation's cities are slowly strangling themselves, jamming together people and industry while spawning pollution, transportation paralysis, housing blight, lack of privacy, and a crimeinfested society. Rural areas simultaneously suffer from the other extreme: lack of sufficient employment opportunities, outmigration and depopulation, and too few people to support services and institutions. The migration from rural areas contributes to the problems of both the city and countryside depopulating rural places at the expense of overcrowded cities.This book focuses on rural development processes, problems, and solutions. Seven prominent specialists in the field, including agricultural and regional economists, demographers, and administrators, discuss the development of the open country, small towns, and smaller cities (up to fifty thousand population). They present an integrated approach to rural development problems, not a mere collection of readings. Valuable guidelines for policies to benefit both rural and urban areas are provided.Since rural development involves interdisciplinary scholarship, this book will be of interest to a wide range of social scientists working in rural areas both here and abroad. Economists, sociologists, and political scientists, as well as community leaders and planners, legislators, government officials and interested laymen, will find this volume useful in understanding the rural development effort.